Imagined futures fictional expectations and capitalist dynamics - Beckert, Jens, 1967- (Harvard University Press, 2016)
"Imagined Futures offers a new explanation for the dynamics of modern capitalism and the restlessness of our economy, based on our temporal orientation. Building on a historical account of how competition and the credit system have forced actors to orient their decisions towards a future that is portrayed and perceived as offering both limitless opportunities and immeasurable risks, Beckert shows how the uncertainty inherent in the future pressures actors to form expectations of distinct outcomes and prevents them from calculating optimal decisions. But how do actors make decisions in a world that contains such fundamental uncertainty? Beckert argues that decisions in the economy are based on imaginaries of the future, which he calls fictional expectations, which allow us to act as if we know the future, providing the reassurance needed to embrace endeavors whose outcomes are unknowable. Beckert shows how these fictional expectations are the underlying force that propels the economy, from investments and the operation of the monetary system to innovations and the purchase of new consumer goods, and how economic crises ensue when these fictional expectations collapse. With its focus on the role of expectations in the economy, Imagined Futures addresses the central macro-level question in the history of the social sciences: What are the sources of the epic growth and repeated crises in modern capitalism?"--Provided by publisher.